Meniscus-assisted solution printing of large-grained perovskite films for high-efficiency solar cells - He, Ming; Li, Bo; Cui, Xun; Jiang, Beibei; He, Yanjie; Chen, Yihuang; O’Neil, Daniel; Szymanski, Paul; EI-Sayed, Mostafa A.; Huang, Jinsong; Lin, Zhiqun (Nature communications, 2017)
Control over morphology and crystallinity of metal halide perovskite films is of key importance to enable high-performance optoelectronics. However, this remains particularly challenging for solution-printed devices due to the complex crystallization kinetics of semiconductor materials within dynamic flow of inks. Here we report a simple yet effective meniscus-assisted solution printing (MASP) strategy to yield large-grained dense perovskite film with good crystallization and preferred orientation. Intriguingly, the outward convective flow triggered by fast solvent evaporation at the edge of the meniscus ink imparts the transport of perovskite solutes, thus facilitating the growth of micrometre-scale perovskite grains. The growth kinetics of perovskite crystals is scrutinized by in situ optical microscopy tracking to understand the crystallization mechanism. The perovskite films produced by MASP exhibit excellent optoelectronic properties with efficiencies approaching 20% in planar perovskite solar cells. This robust MASP strategy may in principle be easily extended to craft other solution-printed perovskite-based optoelectronics. The morphology control of metal halide perovskite crystalline films is of importance to enable high-performance solar cells. Here, He et al . use a meniscus-assisted solution-based method to print microsized perovskite grains at 60 °C, which results in high optoelectronic device efficiency of 20%.